Do institutions mitigate the uncertainty effect on sovereign credit ratings? - Ramírez-Rondán, Nelson R. (2022)
In a more integrated economic and financial world, sovereign credit ratings have become one of the most important factors for countries that seek to access funds in the international bond market. First, we jointly analyzed institutions and uncertainty as determinants of sovereign credit ratings, and second, we tested whether strong institutions soften the impact of uncertainty. Using a sample of 74 countries from 2003 to 2020 for the major agencies Moody’s, Standard & Poor’s, and Fitch, and employing an ordered estimator approach, we find that institutions have a positive effect, whereas uncertainty has a negative effect, and the interaction between them is systematically negative. These results indicate that strong institutions reduce the negative effect of uncertainty on sovereign credit ratings.